2017
DOI: 10.1177/1071100717696360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complete Syndesmotic Disruption and Deltoid Injuries and Different Reduction Methods on Ankle Joint Contact Mechanics

Abstract: Decreased contact area and force with disruption imply that other structures are likely receiving more loads (eg, medial and lateral gutters), which may have clinical implications such as the development of posttraumatic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…2,5,17,18 Despite permitting a flexible syndesmosis, suture button constructs have been shown insufficient for returning joint contact stresses to intact patterns. 16 Though patient-reported outcomes with flexible syndesmotic repairs are nearly always equivalent or superior to those reported for screw fixation, even after screw removal, 7,[13][14][15]34 these improved outcomes appear to be in spite of persistent abnormal ankle biomechanics.…”
Section: Introductionmentioning
confidence: 98%
“…2,5,17,18 Despite permitting a flexible syndesmosis, suture button constructs have been shown insufficient for returning joint contact stresses to intact patterns. 16 Though patient-reported outcomes with flexible syndesmotic repairs are nearly always equivalent or superior to those reported for screw fixation, even after screw removal, 7,[13][14][15]34 these improved outcomes appear to be in spite of persistent abnormal ankle biomechanics.…”
Section: Introductionmentioning
confidence: 98%
“…28 , comparing the transfixation of syndesmosis using a positioning screw with and without conventional reduction forceps (manually combined with crossing K-wires) and the “suture button technique”, the combination with manual reduction and transient K-wire transfixation showed the best results. However, the authors described the differences as minor, similar to our results, and stated that none of the three reduction methods achieved optimal results 28 . Furthermore, in accordance to our study, a complete correction of syndesmosis without significant differences could not be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…All these increasing relative motion of the syndesmosis indicate its stability decreased under the non-anatomical fixation. LaMothe et al [19] demonstrated that the contact stress of the ankle joint was significantly increased after the ligaments were cut off, and the stress histogram revealed that the peak of the contact stress of the talus moved anteriorly and laterally. Moreover, in clinical practice, it was revealed that the unbalanced stress distribution was the main cause of ankle dysfunction and osteoarthritis [20].…”
Section: Discussionmentioning
confidence: 99%